Cultural history of reading - Watling, Gabrielle; Quay, Sara E. (Greenwood Press, 2009)
"Explores what people have read and why they have read it at different times and in different places in America and around the world ... Links key cultural changes and events to the reading material of the period ... Traces reading trends through an exploration of types of texts as well as specific examples of books, magazines, and political treatises that were influential and/or widely read ... Each chapter includes a timeline of events and an introduction to the region/time period that point out major events of the time or region that would have influenced what and how people read. An overview of reading trends and practices traces key trends in reading practices, including the development of lending libraries, the rise of the novel, and the impact of technology. The book also explores the relationship between popular reading materials and cultural change"--Intro., p. [xi].